2021
DOI: 10.1038/s41375-021-01422-y
|View full text |Cite
|
Sign up to set email alerts
|

Transient regulatory T-cell targeting triggers immune control of multiple myeloma and prevents disease progression

Abstract: Multiple myeloma remains a largely incurable disease of clonally expanding malignant plasma cells. The bone marrow microenvironment harbors treatment-resistant myeloma cells, which eventually lead to disease relapse in patients. In the bone marrow, CD4+FoxP3+ regulatory T cells (Tregs) are highly abundant amongst CD4+ T cells providing an immune protective niche for different long-living cell populations, e.g., hematopoietic stem cells. Here, we addressed the functional role of Tregs in multiple myeloma dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 58 publications
0
18
1
1
Order By: Relevance
“…This may explain our results, in which activation of CD8 + T cells, as well as the high abundance of memory T cells, significantly prolongs the OS time of CC patients. Surprisingly, the results showed that high Treg infiltration was significantly associated with good prognosis of patients, which was quite opposite to the phenomenon widely reported thus far ( Banerjee et al, 2021 ; Dahlhoff et al, 2021 ; Peng et al, 2021 ). In previous reports, little literature has mentioned that Treg can participate in the immune process as a protective factor.…”
Section: Discussioncontrasting
confidence: 98%
“…This may explain our results, in which activation of CD8 + T cells, as well as the high abundance of memory T cells, significantly prolongs the OS time of CC patients. Surprisingly, the results showed that high Treg infiltration was significantly associated with good prognosis of patients, which was quite opposite to the phenomenon widely reported thus far ( Banerjee et al, 2021 ; Dahlhoff et al, 2021 ; Peng et al, 2021 ). In previous reports, little literature has mentioned that Treg can participate in the immune process as a protective factor.…”
Section: Discussioncontrasting
confidence: 98%
“…C57BL/6 (“B6”) and FVB/N mice were obtained from Janvier Labs (Le Genest Saint Isle, France). Albino C57BL/6J-Tyr c-2J /J (“B6a”), albino C57BL/6J-Tyr c-2J /Foxp3.Luci.DTR-4 (“FoxP3-Luci-DTR”) ( 21 , 22 ), albino C57BL/6-Tyr c-2J /129S2-Tnfrsf1b tm1Mwm /J (“TNFR2-KO”), FVB/N.L2G85 (“FVB-Luci + ”) and C57BL/6J.L2G85-CD90.1 (“B6-Luci + ”) ( 23 , 24 ), were bred at the Center for Experimental Molecular Medicine (ZEMM) in Würzburg, Germany. All mice were housed in the specific pathogen-free facility of the ZEMM, and experiments were carried out according to the German regulations and reviewed and approved by the governmental authorities (Regierung von Unterfranken, 55.2.2-2532-2-537-61 and 55.2.2-2532-2-410-75).…”
Section: Methodsmentioning
confidence: 99%
“…For in vivo Treg expansion experiments and GvHD studies luciferase-transgenic FoxP3-Luci-DTR mice that express eGFP and luciferase under the FoxP3 promoter ( 21 , 22 ) or B6 WT mice, respectively, were injected intraperitoneally (i.p.) with 140 µg of NewSTAR2 or the same volume of PBS.…”
Section: Methodsmentioning
confidence: 99%
“…On the other side, some reports demonstrate that higher numbers of T-regs in tumors associate with better prognosis in patients [ 172 ], suggesting that the exact prognostic significance of T-regs cells is still unclear, and further studies need to be done. For instance, preclinical studies based on a transient T-reg depletion have demonstrated immune control of MM and prevented disease progression [ 117 ].…”
Section: Impact Of Interactions Between Immune Cells and MM Cells In ...mentioning
confidence: 99%